2022
DOI: 10.7759/cureus.25998
|View full text |Cite
|
Sign up to set email alerts
|

Migraine With Comorbid Depression: Pathogenesis, Clinical Implications, and Treatment

Abstract: Migraine is a neurological disorder that strongly relates to psychiatric conditions like depression. Lately, the increased prevalence of depression in migraineurs has come to attention. This article compiled various literature to explore the association between migraine and depression. Genetic overlap of various gene segments was studied, and heritability patterns were explored. Shared mechanisms such as serotonergic dysfunction, methylenetetrahydrofolate reductase (MTHFR) polymorphisms, and hormonal effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 96 publications
(105 reference statements)
0
11
0
1
Order By: Relevance
“…Many studies have found a link between migraine and depression (39, 40). Migraine is a risk factor for depression, and the incidence and severity of migraine attacks rise during the depression and vice versa (41). Similarly, Jat et al (42) discovered that 6.6% of patients with depression had MA, and 26.1% had MO in crosssectional research.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found a link between migraine and depression (39, 40). Migraine is a risk factor for depression, and the incidence and severity of migraine attacks rise during the depression and vice versa (41). Similarly, Jat et al (42) discovered that 6.6% of patients with depression had MA, and 26.1% had MO in crosssectional research.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results suggest that the right paracentral lobule, left calcarine sulcus, and dorsolateral superior frontal gyrus (SFGdor.L) may be the core region for the development of depression in migraine patients. The study found that (Asif N, Patel A, Vedantam D, et al, 2022) the changes of right paraventral lobule and right fusiform gyrus are the specific manifestations of migraine combined with depression, and the left thalamus, medial orbit of superior frontal gyrus and triangular part of inferior frontal gyrus are all changed in migraine patients. Emotional symptoms of migraine are associated with functional changes in the right paracentral lobule, left talus, and left dorsolateral superior frontal gyrus.…”
Section: Connections Of Brain Structurementioning
confidence: 93%
“…Além disso, atua também de forma agonista na melhora de condições associadas que podem influenciar o tratamento e as recidivas da cefaleia, como doenças metabólicas, mecânicas e mentais (ASIF et al, 2022).…”
Section: -Cefaleia Secundária Associada Ao Esporteunclassified